Effect of Dietary Rumen Protected Methionine on Postpartum Fertility Parameters in Multiparous Dairy Buffaloes (Bubalus bubalis) - Ranjan, Sagar; Singh, Prahlad; Singh, Navdeep; Singh, Narinder; Honparkhe, Mrigank; Grewal, Ravinder Singh; Mohindroo, Jitender (The Indian Journal of Animal Reproduction, 2022)
Present study was planned to assess dietary supplementation of rumen protected methionine (RPM) peripartum on blood profile and postpartum reproductive outcome in 18 multiparous Murrah buffaloes. Animals were randomly assigned to 3 treatment groups of 6 each, and fed diets supplemented with RPM 20 g day-1 (Group 1); 10 g day-1 (Group 2), and standard control diet (Group 3). RPM feeding was introduced from day 30 prepartum till day 60 postpartum. Progesterone, estradiol, IGF-I, and biochemical parameters were estimated starting day 21 prepartum to day 57 postpartum. Size of dominant follicle and corpus luteum were assessed across the treatment days postpartum. Progesterone concentration varied from 0.32±0.06 to 3.85±0.44 ngml-1, 0.41±0.05 to 2.03±0.12 ngml-1, and 0.35±0.08 to 1.82±0.11 ngml-1 in Groups 1, 2 and 3, respectively. Corresponding estradiol levels ranged from 16.00±1.09 to 243.16±4.67 pgml-1, 13.16±0.60 to 228±5.06 pgml-1, and 13.66±0.66 to 218.9±4.36 pgml-1 and IGF-I from 77.83±8.81 to 149.50±4.69 ngml-1, 77.33±2.95 to 128.41±3.85 ngml-1, and 62.66±2.20 to 124.50±5.57 ngml-1 in Groups 1, 2 and 3, respectively. Variations in blood glucose, BUN and creatinine were observed across the days in all the treatment groups. Estrogen to progesterone (E/P) ratio varied (p<0.05) among the treatment groups. Lower values of E/P in Group 1 were depictive of estrogen dominance, whereas higher E/P in Group 3 signified dominance of progesterone. Conception rates in Groups 1, 2 and 3 were 83.33%, 50.00% and 33.33%, respectively. Varying (p<0.05) progesterone and estradiol levels were indicative of positive role of dietary RPM. Dietary RPM improved follicular structures and increased production and reproduction outcomes.